2021
DOI: 10.3171/case21374
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm to improve lateralization accuracy of inferior petrosal sinus sampling: procedural nuances for complex patterns of venous drainage. Patient series

Abstract: BACKGROUND Inferior petrosal sinus sampling (IPSS) is a useful technique in the diagnosis of Cushing’s disease (CD) when the imaging finding is negative or equivocal. Different authors have reported considerable variability in the ability to determine tumor laterality with IPSS. Here the authors present a retrospective case series of 7 patients who underwent IPSS using a systematic algorithm to improve lateralization accuracy by identifying optimal sampling sites on the basis of individual cavernous sinus drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that IPSS results are inaccurate for predicting tumor lateralization due to factors such as intracranial venous system ow patterns [22,23] . A retrospective study of 30 patients by Sun et al found that cavernous sinus sampling results were not associated with intraoperative tumor lateralization ndings [24] .Factors such as asymmetric or dysplastic IPS anatomy and excessive differences in bilateral ductal entry locations have been suggested to in uence the incorrect prediction of tumor lateralization [21,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that IPSS results are inaccurate for predicting tumor lateralization due to factors such as intracranial venous system ow patterns [22,23] . A retrospective study of 30 patients by Sun et al found that cavernous sinus sampling results were not associated with intraoperative tumor lateralization ndings [24] .Factors such as asymmetric or dysplastic IPS anatomy and excessive differences in bilateral ductal entry locations have been suggested to in uence the incorrect prediction of tumor lateralization [21,25] .…”
Section: Discussionmentioning
confidence: 99%